A mulher muçulmana: uma visão panorâmica de Meca a São Paulo - Silva, Dirceu Alves da (2016)
In this research, we´ll turn our eyes to the Muslim women´s world, her trajectory was described in the pre-Islamic period, in the deserts and oases of Arabian Peninsula. Her epic from Mecca even São Paulo city. This period comprise one thousand and four hundred years approximately. Her presence and social, religious and political acting. Her relation with Muhammad, Koran revelation and her fight to gender equality are appointed in this research. Contemplate periods when this woman left her undeniable accomplishments and strong signs of her presence. The research is focused in this woman in different periods: pre-Islamic period, new revelations of Muhammad period, the Muslim khalifat period, the arrival in Brazil period, the slavery period; immigration and conversion to Islam in Brazil. And finally, a special focus to Muslim women in São Paulo city and her religiousness that include cultural habits and her sameness; her conflicts arising from an unequal relationship with male gender. The cultural conflicts and her fight against ethnic-Arabian discrimination and prejudice, beside an Islam more adapted to Brazilian culture. The research was based on qualitative observations, interviews with Muslim women immigrants and descendants, Brazilian women converted to Islam, and visits to mosques in the São Paulo city.